2016
DOI: 10.1097/aap.0000000000000437
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neuraxial Versus General Anesthesia on the Incidence of Postoperative Surgical Site Infections Following Knee or Hip Arthroplasty

Abstract: Synthesis of the existing evidence supports the overall beneficial effects of neuraxial anesthesia in decreasing the development of SSI after joint arthroplasty (KA and HA). Given the limitations associated with interpretation of data from large observational trials, further investigation using prospective randomized trial design is warranted in this promising area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 38 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…29 Furthermore, our findings support those from a meta-analysis of joint arthroplasty procedures showing lower rates of surgical site infection after neuraxial anaesthesia. 30 Conversely, the effects of co-morbidities, such as coronary artery disease, hypertension, and diabetes, have not been replicated following our adjusted analyses. 31,32 This may reflect the fact that the underlying mechanisms behind these co-morbidities may interact and therefore not demonstrate an effect because of loss of statistical power.…”
Section: Discussionmentioning
confidence: 77%
“…29 Furthermore, our findings support those from a meta-analysis of joint arthroplasty procedures showing lower rates of surgical site infection after neuraxial anaesthesia. 30 Conversely, the effects of co-morbidities, such as coronary artery disease, hypertension, and diabetes, have not been replicated following our adjusted analyses. 31,32 This may reflect the fact that the underlying mechanisms behind these co-morbidities may interact and therefore not demonstrate an effect because of loss of statistical power.…”
Section: Discussionmentioning
confidence: 77%
“…Positive pressure ventilation increases intrathoracic pressure during inspiration, which impedes venous return and thereafter facilitates the development of acute kidney injury 35 . Third, neuraxial anesthesia may reduce the risk of surgical site infection through attenuating the stress response to surgery and inducing vasodilation and consequently enhancing tissue oxygenation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…53 Preferential use of neuraxial anesthesia over general anesthesia has also been shown to improve postoperative outcomes. 54,55 In a meta-analysis, that included 16,555 patients, Liu et al demonstrated that patients undergoing knee arthroplasty had a significantly lower incidence of both pneumonia and surgical site infection within a 30 day period, when receiving neuraxial anesthesia compared to general anesthesia. 54 This is believed to be due to the lesser impact that neuraxial anesthesia has on immune function and the comparatively lower degree of surgical stress.…”
Section: Anesthetic Recommendationsmentioning
confidence: 99%